Effect of Eel Lumpia As Additional Food In Pregnant Women With Anemia - Evi Susanti; Rulfia Desi Maria; Lismar Febrianti; Lady Wizia; Tuti Oktriani (Universitas Aisyah Pringsewu, 2023)
Background: The prevalence of anemia in pregnant women is high, 4 out of 10 pregnant women experience anemia during pregnancy, 70% of which is mild anemia and occurs during pregnancy. Iron deficiency in the body, brought on by a lack of iron-containing foods, is the primary cause of anemia in pregnant women. Purpose: This research intends to assess the impact of eel spring rolls on the hemoglobin levels of anemic pregnant women. Methods: This quasi-experimental study used a one-group pre-test and post-test design. This research was conducted in the Community Health Center in Sungai Penuh. The sample in this study were all pregnant women with anemia who were taken using a sampling technique, namely total sampling. The intervention by giving eel spring rolls was carried out for 21 days, weighing 350 grams of eel spring rolls/day. Hemoglobin levels were measured twice, before and after the intervention. Data analysis was performed using a paired t-test to see the difference in the average pretest and posttest scores. Results: there is an effect of giving Eel Lumpia as additional food on changes in hemoglobin levels in Pregnant Women with Mild Anemia in Health Center work area in 2022. Conclusion: It is hoped that health workers can provide education about consuming eel as an additional food that pregnant women can use to prevent anemia in pregnant women.Abstrak: Latar belakang: Prevalensi anemia kejadian anemia pada ibu hamil tergolong tinggi, 4 dari 10 ibu hamil mengalami anemia selama kehamilan, 70% nya merupakan anemia ringan dan terjadi pada timester III kehamilan. Penyebab langsung terjadinya anemia di wanita hamil merupakan kekurangan zat besi di dalam tubuh yang ditimbulkan oleh kurangnya sumber makanan yang mengandung zat besi. Tujuan: Penelitian ini berujuan untuk mengetahui pengaruh konsumsi lumpia belut terhadap kadar hemoglobin ibu hamil dengan anemia. Metode: Penelitian quasi eksperimen ini menggunakan rancangan one group pre-test post-test design. Tempat penelitian ini adalah Puskesmas di Sungai Penuh. Sampel dalam penelitian ini adalah semua ibu hamil dengan anemia yang diambil dengan teknik pengambilan sampel yaitu total sampling. Intervensi pemberian lumpia belut dilakukan selama 21 hari, dengan 350 gram lumpia belut/hari. Pengukuran kadar hemoglobin dilakukan dua kali, sebelum dan sesudah intervensi. Analisis data dilakukan menggunakan uji paired t-test untuk melihat perbedaan nilai rata-rata pre- test dan post- test. Hasil: ada pengaruh pemberian PMT Lumpia Belut terhadap perubahan kadar hemoglobin pada Ibu Hamil dengan Anemia Ringan di wilayah kerja Puskesmas Sungai Penuh tahun 2022. Kesimpulan: Diharapkan tenaga kesehatan dapat memberikan edukasi tentang konsumsi belut sebagai salah satu makanan tambahan yang bisa digunakan oleh ibu hamil sebagai preventif anemia pada ibu hamil.